FOURIER COEFFICIENTS FOR THE LIGHT CURVES OF 62 MIRA-TYPE STARS - Kudashkina, L. S.; Andronov, I. L. (Одеські астрономічні публікації, 2017)
For 62 Mira-type stars the values of periods have been redetermined; the mean curves have been fitted by a trigonometric polynomial with an optimal number of harmonics; a number of the parameters of the light curve have been calculated (amplitude of the present harmonic in stellar magnitudes, phase of the maximum of the amplitude of the present harmonic, ratio of the amplitude of the harmonic to the amplitude of the main harmonic wave, shift of the phase of the present harmonic relatively to the main wave, shift of the phase of the present harmonic relatively to the maximum of brightness). The parameters of the sharpness of the both branches of the light curve are obtained: the time of the brightness changes by 1 mag, the ratio between the maximal slope of the incline to the derivative for sinusoidal signal with present amplitude and period. All these parameters are tabulated.